Gangguan Berbahasa Pada Penderita Strok Suatu Kajian: Neurolinguistik - Mhd. Johan; Alpino Susanto (Prosiding, 2018)
Neurolinguistic studies are a study in which humans how to acquire language. The purpose of this study is to explain the level where the phoneme is pronounced by the respondent. The theory used is a neurolinguistic theory initiated by Claudia Galluzzia and friends. Meanwhile, the method of data collection is a method by using recording technique. In addition, to analyze this data, the authors use the agih method or contribution method by using the basic technique for the direct element. Technique consists of the technique of percolation, change technique or technique of addition, After the analysis is done then obtained the results. The results of this study include a more dominant change process found in the respondent's speech and the second dominant process is the process of exploitation and the last is the process of addition. Details of the results of this study are: the process of percolation there are 5 times, the addition process there are 4 times whereas the change process there are 11 times. The percentage of the results is 25% (twenty five percent) of the process of discontinuation, the addition process consists of 20% (twenty percent), while the change process is 55% (fifty five percent) using the following formula divided by the total problem multiplied by 100 percent.